Small Medium-Sized Enterprises (SMEs) to hypermarkets: critical quality aspects in delivering food and beverage products - Abdul, Mohani; Ab Rahman, Rozanah; Kamarulzaman, Nitty Hirawaty; Ibrahim, Saadiatul; Rahman, Mohammad Mizanur; Uddin, Mohammad Jamal (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Small and Medium-Sized Enterprises (SMEs) play a significant role in the economic growth and development in Malaysia. According to the Malaysian Standard of Industrial Classification (2008), food and beverage is a sub-sector of the manufacturing sector, which is the second largest concentration of SMEs. This study focused on SME entrepreneurs in order to gather their thoughts on imparting quality in their products to penetrate the Malaysian hypermarkets. Primary data were gathered from 426 SME entrepreneurs using a structured questionnaire. Independent and dependent variables were formed on a five-point Likert-type scale which specifies the strength of the respondents’ agreement or disagreement with the statements provided. Several statistical tools and techniques, such as descriptive statistics, Zero Order Karl Pearson’s correlation and Ordinary Least Square (OLS) multiple regression analysis were used to analyse the findings and to draw conclusions. The study revealed that food and beverage entrepreneurs gave more emphasis on the esthetics aspect of the products to expand their businesses and to enter hypermarkets. Entrepreneurs who have yet to supply their products to hypermarket focused on more aspects (e.g. product performance, food features, conformance to specifications and reliability of the product) than entrepreneurs who have already been supplying their products to hypermarkets. The findings of this study will assist SME entrepreneurs and the Malaysian SME authority who are working towards expanding their products, especially on food and beverages and for those thinking of penetrating hypermarkets with their products.